2013
DOI: 10.15517/rbt.v61i1.10938
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and morphometric relationships of the sagitta of <i>Diapterus auratus</i> (Perciformes: Gerreidae) from Veracruz, Mexico

Abstract: Sagittae otoliths are the most studied because of their morphological variability and size; the sagittae may also have valuable taxonomic use and for D. auratus has not yet been described. In the present study we present a morphological description of the sagitta otolith and an analysis of its correlation with various morphometric parameters. The biological material was captured with a beach seine in the coasts of Alvarado and Port of Veracruz, from November 2009 to June 2010. Sagittae were extracted, cleaned,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…Similar studies have examined the relationship between gerreid fish weight and sagittal length. For example, Rivera-Félix et al (2013) found a positive allometric relationship between otolith length and fish weight for the Irish mojarra D.auratus, in contrast to the negative allometric relationship observed in the present study. However, in the previous study, the linear relationship between fish length and the length of otoliths was not evaluated, but their approach considered the otolith length a depended variable (Rivera-Felix et al 2013: Figure 2A, 2B, 2C, 2D, 2E).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar studies have examined the relationship between gerreid fish weight and sagittal length. For example, Rivera-Félix et al (2013) found a positive allometric relationship between otolith length and fish weight for the Irish mojarra D.auratus, in contrast to the negative allometric relationship observed in the present study. However, in the previous study, the linear relationship between fish length and the length of otoliths was not evaluated, but their approach considered the otolith length a depended variable (Rivera-Felix et al 2013: Figure 2A, 2B, 2C, 2D, 2E).…”
Section: Discussioncontrasting
confidence: 99%
“…To the best of our knowledge, the relationships between size parameters in fish and otolith length for species of the Gerreidae family that inhabit the coast of Mexico have not been investigated, except for three species: the Irish mojarra Diapterus auratus Ranzani 1842, the short-nosed mojarra D. brevirostris (Sauvage 1879), and the yellowfin Mojarra Gerres cinereus (Walbaum 1792) (Rivera-Félix et al 2013;Gallardo-Cabello et al 2014;Espino-Barr et al 2015, respectively). In contrast, these relationships have been examined in other fish families (e.g., AuriolesGamboa, 1992;Espino-Barr et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The otolith length (Waessle et al 2003;Zengin et al 2015), otolith breadth (Kumar et al 2017) and otolith weight (Bostanci et al 2011;Zengin et al 2017) can be calculated as the best indicator for predicting fish size. Otolith biometry-fish length relationships have been determined for some freshwater and marine fishes (Harvey et al 2000;Battaglia et al 2010;İlkyaz et al 2008;Mata et al 2008;Mamry et al 2010;Jawad et al 2011;Basusta et al 2013;Felix et al 2013). However, the right and left otoliths may not provide the same results of prey fish length estimates (Harvey et al 2000;Waessle et al 2003;Kumar et al 2012).…”
Section: Discussionmentioning
confidence: 99%